2001
DOI: 10.1021/jo001640n
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of a Conformationally Constrained Didemnin B Analog

Abstract: The total synthesis of a didemnin B analogue containing a conformationally constrained replacement for the isostatine moiety is reported. Synthetic highlights include an improved preparation of 2-hydroxy-3-cyclohexenecarboxylic acid and a new strategy for accessing the macrocycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Cys189 also controls the multimerization of CTR1 (Eisses and Kaplan, 2002;Lee et al, 2007;Sinani et al, 2007). The relative binding affinities are such that the C-terminal end of CTR1 can transfer copper to ATOX1 and presumably also to copper chaperone for superoxide dismutase and cytochrome c oxidase assembly homolog (Xiao et al, 2001), although binding of ATOX1 to CTR1 has not actually been demonstrated.…”
Section: Structure and Copper Transport Function Of Ctr1mentioning
confidence: 99%
“…Cys189 also controls the multimerization of CTR1 (Eisses and Kaplan, 2002;Lee et al, 2007;Sinani et al, 2007). The relative binding affinities are such that the C-terminal end of CTR1 can transfer copper to ATOX1 and presumably also to copper chaperone for superoxide dismutase and cytochrome c oxidase assembly homolog (Xiao et al, 2001), although binding of ATOX1 to CTR1 has not actually been demonstrated.…”
Section: Structure and Copper Transport Function Of Ctr1mentioning
confidence: 99%
“…The group later synthesized another conformationally constrained analogue, in which the isostatine moiety was replaced by a (S,S,S)-b-hydroxyg-aminocyclohexanecarboxylic acid, to probe the biological conformation of didemnin B. 78 The constrained analogue (11) was tested for protein biosynthesis inhibition and showed about 20-fold decrease in activity, compared to didemnin B.…”
Section: Modifications In the Hip-isostatine Regionmentioning
confidence: 99%
“…Joullié and co-workers reported the synthesis of chiral cyclohexane carboxylic acid 7 (R = H) by a Diels-Alder reaction between camphor sultam derived acrylic acid derivative 8 and 1-acetoxy-1,3-butadiene ( 9) under two conditions: toluene reflux and 5M LiClO 4 in Et 2 O at room temperature. 7 We examined both conditions and found that separation of the isomers obtained under the toluene reflux conditions was difficult on a larger scale, while the Diels-Alder reaction in 5M LiClO 4 in Et 2 O was very slow (the reaction had not completed even after 8 days), although the diastereoselectivity was very high as reported. We thus abandoned the Diels-Alder reaction between 8 and 9 in this study.…”
Section: Letter Syn Lettmentioning
confidence: 77%